PENGARUH MEDIA PEMBELAJARAN BERBASIS WEB WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V UPT SPF SDN 105275 PAYA GELI - Lainatussifa; Wildansyah Lubis; Winara; Tiarnita Maria Sarjani Br. Siregar; Masta Marselina Sembiring (STKIP Subang, 2025)
This study aims to determine the effect of Web-Based Learning Media Wordwall on the Indonesian language learning outcomes of Grade V students at UPT SPF SDN 105275 Paya Geli. The research employed a quantitative approach with a quasi-experimental design using the Non-Equivalent Control Group Design. The sample consisted of 45 students, with class V-A (23 students) as the experimental group and class V-B (22 students) as the control group. The research instrument included pre-test and post-test, which were tested for validity, reliability, difficulty level, and discriminating power. Data were analyzed using the Normality Test, Homogeneity Test, and Hypothesis Test. The results showed that students' average learning outcomes without using Wordwall were 47.3, while those using Wordwall achieved 87.3. The normality test results showed the data were normally distributed, with Sig. values of 0.127 (pre-test) and 0.066 (post-test), both greater than 0.05. The homogeneity test also indicated that the data were homogeneous (Sig. = 0.195 > 0.05). The hypothesis test using post-test scores showed tcount = 2.718 > ttable = 2.0167 at a significance level of 0.05, leading to the acceptance of Ha and rejection of Ho. It can be concluded that Web Wordwall-Based Learning Media significantly influences the Indonesian language learning outcomes of Grade V students at UPT SPF SDN 105275 Paya Geli.